An assessment of the prevalence of Aflatoxin M1 level in milk and milk powder based on high performance liquid chromatography and dietary risk assessment - Yaser Almasoud; Manar Alwelaie; Zeyad Aldosari; Sarah Alotaibi; Abdullah Alsayari; Ghada Alzyadi; Mohammed Almutairi; Sulaiman Alajel; Abdullah Al Tamim; Hibah Alharbi (Toxicology Reports)
Milk is susceptible to Aflatoxin M1 (AFM1) contamination, mainly through consumption of contaminated animal's feed. The natural occurrence of aflatoxin M1 (AFB1) has been surveyed in samples of milk and milk powder. Samples collected from different regions of Saudi Arabia during the period from 2013 to 2021 were subjected to high-performance liquid chromatography analysis, and (AFB1) was quantified with detection limits of 0.5 µg/kg. The Saudi Food and Drug Authority has taken strong actions to limit AFM1 contamination, increase aflatoxin control, and modify the regulations. A study analyzed 363 randomly collected milk samples (168 milk, 195 milk powder) from Saudi Arabia using LC-MS/MS. Out of the 363 samples, 20 were positive for AFM1, with 343 were within the limits. One out of the 168 milk samples and 19 out of the 195 milk powder samples exceeded the limits, with seven originating from Saudi Arabia. The highest AFM1 concentration (3.97 µg/kg) was found in the Saudi samples. Saudi Arabia's mycotoxin regulations significantly reduced AFM1 contamination in milk, which is not considered a serious health hazard.